The Effect of Physiotherapy on Pain Intensity in Patients with Low Back Pain (LBP) in Adults at Kabanjahe Hospital in 2025 - Deo Jordy Barus; Masdalena Nasution; Juliana Lina (Eduvest - Journal of Universal Studies, 2025)
Low Back Pain (LBP) is one of the musculoskeletal disorders commonly experienced by adults due to unergonomic posture, excessive activity, and degenerative processes. This condition causes pain in the lower back which can hinder daily activities and reduce the quality of life. This study aims to determine the effect of physiotherapy on pain intensity in LBP patients at Kabanjahe General Hospital in 2025. The research method used was descriptive analytics with a cross-sectional design. The sample amounted to 100 adult respondents who were selected using purposive sampling techniques. Data was collected through questionnaires and Visual Analogue Scale (VAS) measurements, then analyzed using the Chi-Square test. The results showed a significant difference between pain intensity before and after physiotherapy (p = 0.001). There was a decrease in the proportion of severe pain from 30% to 10% and an increase in mild pain from 20% to 60% after physiotherapy. Of the three modalities used—InfraRed (IR), Transcutaneous Electrical Nerve Stimulation (TENS), and William Flexion Exercise—TENS provided the most effective results in reducing pain (75%), followed by IR (70%) and William Flexion Exercise (65%). Risk factors such as old age, long working hours, high body mass index, and poor posture also affect pain levels. In conclusion, physiotherapy has been shown to be effective in reducing pain intensity in LBP sufferers, particularly through a combination of electrotherapy modalities and regular physical exercise.